International experience and national peculiarities of protection of the right to access to information: comparative legal analysis - Digay, D.A.; Tleshaliyev, N.D.; Persheyev, A.S. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The work explores the evolution of the right of access to information, analyzes international standards and national models of its implementation, and considers challenges and prospects in this area. The research contributes to the development of the theoretical foundations of the right to access to information and provides practical recommendations for its improvement. The research employs a approach to examine global and local legal statutes and court precedents alongside the practices of various nations in guarantee of information access rights. The study demonstrates that access, to information is a entitlement and a crucial component of a democratic community. The authors identify key international standards in this area, as well as analyze differences in national approaches to the implementation of this right. Special attention is paid to the challenges associated with the protection of state secrets, confidential information and personal data. The research categorizes data regarding the rights to access information and investigates procedures while acknowledging the national traits, in its implementation process. The results of this study can be used to improve legislation and regulations and develop programs to educate the public about their right to access information.